Carex linanensis (sect. Mitratae), a new species of Cyperaceae from Zhejiang, East China - Xiang-Dong Qiu; Yi-Fei Lu; Xiao-Feng Jin (PhytoKeys, 2024)
Carex linanensis X.D.Qiu & X.F.Jin, a new species in sect. Mitratae of the sedge family (Cyperaceae) from north-western Zhejiang is described and illustrated. We performed a statistical comparison of the new species with other closely-related species from the same section. Carex linanensis is similar to Carex sachalinensis F.Schmidt, but differs in having leaf blades 1–2 mm wide (vs. 2.5–3.5 mm wide), utricles longer than pistillate glumes, with beak margin smooth (vs. barbate) and peduncles of lateral spikes enclosed in bract sheaths (vs. exserted from bract sheaths).